1998
DOI: 10.1007/s001470050503
|View full text |Cite
|
Sign up to set email alerts
|

One-way donor-recipient HLA-matching as a risk factor for graft-versus-host disease in living-related liver transplantation

Abstract: Although one-way matching between an HLA-homozygous donor and a haploidentical recipient is a recognized risk factor in transfusion-associated graft-versus-host disease (GVHD), its impact in living-related liver transplantation (LRLT) has so far not been investigated. We present a case of fatal acute GVHD in our LRLT program that was attributed to one-way HLA matching between donor and recipient. Although the disappearance of donor cells in peripheral blood was suggested by genetic analysis, severe septicemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Previous reports have implicated quantitative or functional recipient lymphocyte deficiencies, with suggested predisposing risk factors including increasing recipient age, preexisting immunosuppressive states, low preoperative lymphocyte count, and the number of mismatched HLA specificities (10,14,16,21). The Kyoto group reported four cases of GvHD after living-related donor liver transplantation associated with one-way HLA compatibility caused by donor homozygosity (22). There is also evidence linking alcohol abuse and nonspecific immunosuppression with a lower incidence of acute rejection (23), but the literature does not uniformly support this (24).…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports have implicated quantitative or functional recipient lymphocyte deficiencies, with suggested predisposing risk factors including increasing recipient age, preexisting immunosuppressive states, low preoperative lymphocyte count, and the number of mismatched HLA specificities (10,14,16,21). The Kyoto group reported four cases of GvHD after living-related donor liver transplantation associated with one-way HLA compatibility caused by donor homozygosity (22). There is also evidence linking alcohol abuse and nonspecific immunosuppression with a lower incidence of acute rejection (23), but the literature does not uniformly support this (24).…”
Section: Discussionmentioning
confidence: 97%
“…A number of publications indicated that a closely HLAmatched donor-recipient transplant has been considered be a risk factor for GVHD after liver transplant (4,28). A close HLA matching may reduce the antigenicity of donor cells and thus impair recognition and clearance of donor cells from the recipient circulation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the pediatric case that is included in this review with complete one-way HLA matching died from GVHD. 10 On the contrary, few cases (5 out of 906 LT pairs) with donor-dominant one-way matching in one or two HLA loci did not demonstrate GVHD post-LT. 1 This study suggested that the total number of HLA loci with donordominant one-way HLA matching, including HLA-C, 3 is an important risk factor for GVHD post-LT. This emphasizes the importance of pre-transplant HLA typing for donor selection and in predicting GVHD post-LT.…”
Section: Discussionmentioning
confidence: 96%